2008
DOI: 10.1002/hep.22648
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of randomized trials for hepatocellular carcinoma treated with percutaneous ablation therapies

Abstract: According to the American Association for the Study of Liver Diseases guidelines, percutaneous ethanol injection (PEI) is a safe and highly effective treatment for small hepatocellular carcinomas (HCC) and should be the standard against which any new therapy is compared. The primary purpose of this study was to identify survival benefit of any percutaneous ablation therapy as compared with PEI in the treatment of patients with unresectable HCC. The secondary endpoints were initial tumor response, local tumor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
244
1
13

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(269 citation statements)
references
References 42 publications
5
244
1
13
Order By: Relevance
“…In a study of 232 patients (118 treated with RFA and 114 treated with PEI), the 4-year survival rate was 74% (95% confidence interval [CI] 65-84) for RFA and 57% (95% CI 45-71) for PEI, with a 46% smaller risk of death (adjusted relative risk, 0.54 [95% CI 0.33-0.89], P = 0.02), a 43% smaller risk of overall recurrence (adjusted relative risk, 0.57 [95% CI 0.41-0.80], P = 0.0009), and an 88% smaller risk of local tumor progression (relative risk, 0.12 [95% CI 0.03-0.55], P = 0.006) with RFA than with PEI [6]. Similarly, longer survival has also been suggested by the analysis of a subgroup trial in Taiwan [7], and Cho et al [8] have reported that RFA demonstrates significantly improved 3-year survival status by the meta-analysis of four randomized controlled trails. Moreover, RFA requires shorter hospitalization than PEI, which improves the quality of life.…”
Section: Discussionmentioning
confidence: 72%
“…In a study of 232 patients (118 treated with RFA and 114 treated with PEI), the 4-year survival rate was 74% (95% confidence interval [CI] 65-84) for RFA and 57% (95% CI 45-71) for PEI, with a 46% smaller risk of death (adjusted relative risk, 0.54 [95% CI 0.33-0.89], P = 0.02), a 43% smaller risk of overall recurrence (adjusted relative risk, 0.57 [95% CI 0.41-0.80], P = 0.0009), and an 88% smaller risk of local tumor progression (relative risk, 0.12 [95% CI 0.03-0.55], P = 0.006) with RFA than with PEI [6]. Similarly, longer survival has also been suggested by the analysis of a subgroup trial in Taiwan [7], and Cho et al [8] have reported that RFA demonstrates significantly improved 3-year survival status by the meta-analysis of four randomized controlled trails. Moreover, RFA requires shorter hospitalization than PEI, which improves the quality of life.…”
Section: Discussionmentioning
confidence: 72%
“…There es supporting R dard of care f be clearly seen n the surround latest improve erstandable tha HCC > 3 cm, t m [45,46] . In suc ve survival [44 ns that clinicia effusion and p eligible patient bility of incom in relation to mplete necrosis sular or within [43] [52,53] ) -accounting for 10%-15% of tumors [1] .…”
Section: Radiofreqmentioning
confidence: 93%
“…13,14 There is a trend to superior results with RFA over PEI. 15,16 The specific modality used is often based on institutional preference but there are also anatomical considerations. For example, exophytic lesions, subcapsular lesions, or lesions near intrahepatic vessels lend themselves less accessible to RFA, and TACE may be preferred.…”
Section: The Problemmentioning
confidence: 99%
“…In addition, the failure rate for PEI and RFA is higher with increase in the size of the lesions (>3 cm). 15,16 Multifocal disease often lends itself to TACE, but in some institutions RFA is still performed. In addition, poor liver function is a contraindication to locally ablative treatment as well.…”
Section: The Problemmentioning
confidence: 99%